(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Bharati Mukherjee’s fiction is an important part of diasporic and multicultural literature due to the very strong depiction of immigration, assimilation, cultural conflict and identity transformation. Her novels and short stories vividly depict the lives of South Asian immigrants, especially Indian women, who grapple with the social and cultural environments they find themselves in when they are away from home. The paper explores Mukherjee’s approach to immigration and multiculturalism in some of her selected books including The Tiger’s Daughter, Wife, and Jasmine. The study is focused on the psychological implications of displacement, the crisis of identity and the assimilation aspect of immigrant characters that are situated between the East and the West. In this work, Mukherjee introduces the subject of immigration as both a problem and a chance for transformation, as people find themselves in multiple identities in multicultural societies. Her works also condemn "cultural purity" and advocate for "hybridity," "fusion," and "cross-cultural adaptation. With a dynamic and transformative portrayal of the immigrant experience, Mukherjee is in a position to redefine the concept of the American identity and focus on the contributions immigrants made to multicultural societies. The paper concludeIdentity Crisiss that Mukherjee’s fiction is a celebration of resilience, adaptability and cultural fusion, but also of the emotional and social complexities of diaspora life.